2014
DOI: 10.1111/tmi.12362
|View full text |Cite
|
Sign up to set email alerts
|

Leprosy in Brazil and its association with characteristics of municipalities: ecological study, 2009–2011

Abstract: Abstractobjective To analyse the ecological association between the demographic and socio-economic characteristics of the Brazilian municipalities and average leprosy incidence rate in the period 2009-2011.methods An ecological study taking the Brazilian municipalities as its units of analysis. The local empirical Bayes estimation method was used to obtain smoothed incidence rates (SIR) for leprosy. The mean, median, first quartile (Q1) and third quartile (Q3) of the SIR were calculated per 100 000 inhabitants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
67
2
26

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 21 publications
7
67
2
26
Order By: Relevance
“…The importance of intra-domiciliary transmission was confirmed by comparing it with the probability that multibacillary carriers will be infected even before the clinical manifestation of the disease 17,35,46 . Transmission was also identified in the neighborhood and school environment 39,45 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…The importance of intra-domiciliary transmission was confirmed by comparing it with the probability that multibacillary carriers will be infected even before the clinical manifestation of the disease 17,35,46 . Transmission was also identified in the neighborhood and school environment 39,45 .…”
Section: Discussionmentioning
confidence: 98%
“…In t h e a n a l y s e s b y municipalities, three studies examined the N CDR of the country at different moments in time 10,16,17 , and showed concentration in the North and Midwest regions, and in the Northeastern states located in Legal Amazon. The study by Freitas et al 17 To homogenize results, we described NCDR for 100,000 inhabitants and CP for 10,000 inhabitants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations